Negative electrode active material for secondary battery, method of preparing the same, negative electrode for secondary battery and lithium secondary battery comprising the same
Patent Information
- Application Number
- JP2024138432
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-28
- Filing Date
- 2024-08-20
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2044-08-20
AI Technical Summary
【0032】 本発明では、前処理した炭素系粒子を使用することによって、炭素系粒子の表面に形成された凹凸構造(defect)によってマイクロ波吸収能力を向上させることができる。炭素系粒子に全体的に均一な温度上昇と急速加熱/冷却とが可能なので、SiC合成反応が起こる温度範囲(約900℃)の滞留時間(維持時間)を減らすことができ、SiC合成量を減少させることができる。
Smart Images

Figure 2025032989000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material for a secondary battery, a method for producing the same, a negative electrode for a secondary battery, and a lithium secondary battery including the same. [Background technology]
[0002] Recently, technological development for mobile devices is expanding as the demand for electronic devices such as mobile devices increases. Demand for lithium secondary batteries such as lithium batteries, lithium ion batteries, and lithium ion polymer batteries as the power source for such electronic devices is increasing significantly. In addition, the growth of the electric vehicle market is accelerating as regulations related to automobile fuel efficiency and exhaust gas become stricter around the world. Accordingly, it is expected that the demand for medium- and large-sized secondary batteries such as secondary batteries for electric vehicles (EVs) and secondary batteries for energy storage systems (ESSs) will soar.
[0003] Recently, as the demand for high-capacity secondary batteries, such as medium- and large-sized secondary batteries, has increased, silicon-based negative electrode materials with excellent theoretical capacity have been researched as negative electrode materials for secondary batteries. However, silicon-based negative electrode materials have problems such as large volume changes during lithium insertion / extraction, electrical desorption due to silicon particle pulverization, and loss of reversible capacity during repeated charge / discharge cycles.
[0004] In order to solve the problem of mechanical damage to electrodes caused by the volume expansion and contraction of silicon and the resulting rapid shortening of lifespan, research is being conducted into methods of compositing different materials that can buffer the volume expansion of silicon and methods of manufacturing silicon into nanoparticles to improve performance. In particular, active development is being conducted in terms of technology for the process of compositing silicon (nano)particles with graphite and commercialization to reduce the cost of the silicon nanoparticle manufacturing process.
[0005] The present invention relates to a method for manufacturing a composite anode material in which nano-sized silicon and a carbon-based material are combined in a single process, and provides a method for manufacturing a silicon-carbon composite in which silicon nanoparticles are formed on the surface of carbon using microwaves. Silicon has a melting point of 1414°C, and when melted, its density increases more than when it is in a solid state like water. Graphite (carbon-based material) exhibits the characteristic of suddenly generating heat when the π electrons present in the structure are alternately induced to be negative (-) and positive (+) using microwaves (wavelength 1m-1mm; frequency 300MHz-300GHz). By applying this phenomenon, silicon, which has a lower melting point than graphite, can be melt-processed on the surface of graphite, and a silicon nanomaterial (graphite combined with nanosilicon) with an increased specific surface area on the surface of graphite can be manufactured by suddenly increasing entropy due to the rapid energy transfer.
[0006] The method for manufacturing silicon-carbon composites using microwaves is a method of directly transferring energy to the surface of carbon, and regardless of the medium that supports the carbon material, when microwaves are irradiated, only the temperature of the carbon itself rises rapidly, and when microwave irradiation is stopped, it cools rapidly. This has the advantage of reducing manufacturing time and energy costs compared to conventional heating methods.
[0007] However, because energy is only transferred to the area irradiated with microwaves, silicon nanoparticles are not formed uniformly on the entire surface of the carbon (graphite), or the impregnated silicon particles become coarse and thin. In this case, it is difficult to adequately buffer the volume expansion of silicon particles when lithium is inserted / deintercalated.
[0008] In addition, silicon carbide (SiC), which is synthesized at high temperatures of over 900°C, is produced as a by-product on the surface of carbon (graphite) when it is rapidly heated to around 1,400°C by microwaves. This silicon carbide is inactive to lithium ions and prevents the lithium ions from diffusing into silicon particles, which leads to a decrease in capacity and efficiency. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Registration 10-2133961 B1 [Patent Document 2] Korean Patent Registration 10-1929413 B1 [Patent Document 3] Korean Patent Registration 10-2063809 B1 [Patent Document 4] Korean Patent Registration 10-1931143 B1 Summary of the Invention [Problem to be solved by the invention]
[0010] The object of the present invention is to provide a Si / C composite and a manufacturing method thereof, which are manufactured through a sintering process using microwaves. The technical feature of the method is that the process of manufacturing silicon nanoparticles and the process of compositing silicon with a carbon-based material (Si / C composite) are carried out in a single process.
[0011] Another object of the present invention is to improve the microwave absorption ability of carbon (graphite), thereby suppressing the coarsening and thinning of silicon particles impregnated on the surface of the carbon, and to uniformly form silicon nanoparticles all over the carbon surface. Another object of the present invention is to provide a Si / C composite that suppresses the generation of silicon carbide (SiC), which is an inactive substance, and has an improved initial charge / discharge capacity. [Means for solving the problem]
[0012] According to an embodiment of the present invention, there is provided an anode active material comprising a silicon / carbon (Si / C) composite having a silicon-based coating layer formed on carbon-based particles, the Si / C composite having a peak area ratio A2 / A1 of 0.2 to 3.0 as measured by X-ray diffraction analysis, where A1 may be the area of a Si peak as measured by X-ray diffraction analysis, and A2 may be the area of a SiC peak as measured by X-ray diffraction analysis.
[0013] The Si / C composite may have a peak area ratio A2 / A1 of 0.3 to 0.5 as measured by X-ray diffraction analysis, where A1 is the area of a Si peak as measured by X-ray diffraction analysis, and A2 is the area of a SiC peak as measured by X-ray diffraction analysis.
[0014] In the Si / C composite, a Si peak area (A1) relative to a total peak area (100%) may be 2 to 7% and a SiC peak area (A2) may be 0.5 to 5.5% in an X-ray diffraction analysis.
[0015] The Si / C composite has a BET specific surface area (B2) of 8m 2 / g or more.
[0016] The Si / C composite has a BET specific surface area (B2) of 8 to 23 m 2 / g.
[0017] The Si / C composite may have a ratio of BET specific surface areas B2 / B1 of 1 or more. The B1 may be the BET specific surface area of carbon-based particles before a silicon-based coating layer is formed in the Si / C composite, and the B2 may be the BET specific surface area of the Si / C composite.
[0018] The Si / C composite may have a BET specific surface area ratio B2 / B1 of 1.2 to 2.5, where B1 may be the BET specific surface area of carbon-based particles before a silicon-based coating layer is formed in the Si / C composite, and B2 may be the BET specific surface area of the Si / C composite.
[0019] The Si / C composite may have a specific surface area contribution rate (B2_C) of the carbon-based particles of 50 to 89.5% relative to a total BET specific surface area (B2) of 100%, and a specific surface area contribution rate (B2_Si) of the silicon-based coating layer of 10.5 to 50%.
[0020] The Si / C composite may have a BET specific surface area contribution rate (B2_C) of the carbon-based particles of 60 to 80% relative to a total BET specific surface area (B2) of 100%, and a BET specific surface area contribution rate (B2_Si) of the silicon-based coating layer of 20 to 40%.
[0021] The silicon-based coating layer may contain silicon nanoparticles having a size of 1 to 100 nm.
[0022] The silicon-based coating layer may be included in an amount of 5 to 50 wt % based on the total weight of the Si / C composite.
[0023] The silicon-based coating layer may be formed to a thickness of 10 to 200 nm.
[0024] The carbon-based particles may be at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers, and hard carbon.
[0025] The carbon-based particles are measured using a color difference meter. * The value may be 35 or less.
[0026] Another embodiment of the present invention provides a method for preparing a negative electrode active material for a secondary battery, the method including: a pretreatment step of heat-treating carbon-based particles; and a microwave firing step of mixing the heat-treated carbon-based particles and silicon-based particles and irradiating the mixture with microwaves.
[0027] The pretreatment step may involve heat treating the carbon-based particles at 400 to 900° C. for 1 to 10 hours.
[0028] The microwave calcination step may involve rapidly heating the surfaces of the heat-treated carbon-based particles with microwaves, and melting the silicon-based particles by the microwave-heated carbon-based particles to form a silicon-based coating layer on the surfaces of the carbon-based material.
[0029] The microwave heating may involve irradiating microwaves at an output of 1 to 3 kW for 10 seconds to 10 minutes.
[0030] Another embodiment of the present invention provides a negative electrode for a secondary battery, comprising the negative electrode active material.
[0031] Another embodiment of the present invention provides a secondary battery including the negative electrode. Effect of the Invention
[0032] In the present invention, the use of pretreated carbonaceous particles improves microwave absorption capability due to the uneven structure (defect) formed on the surface of the carbonaceous particles.Since the carbonaceous particles can be uniformly heated and rapidly heated / cooled, the residence time (maintenance time) in the temperature range (about 900°C) where the SiC synthesis reaction occurs can be reduced, and the amount of SiC synthesis can be reduced.
[0033] In addition, in the present invention, the uneven structure (defects) on the surface of the pretreated (heat-treated) carbon-based particles can be used to control the manner in which molten silicon precipitates (impregnates) on the surface of the carbon-based particles, thereby preventing the coarsening of silicon particles and the connection (thinning) between particles.
[0034] In addition, by controlling the BET specific surface area of the Si / C composite within a specific range, silicon particles can be uniformly dispersed and impregnated on the surface of the carbon-based particles in nano size, which prevents the silicon particles from becoming coarse or being impregnated in the form of a thin film. As a result, the problem of electrolyte side reactions caused by an excessive increase in the specific surface area can be improved. [Brief description of the drawings]
[0035] [Figure 1a] 1 is a SEM image of the surface of a Si / C composite produced in Comparative Example 1. [Figure 1b] 1 is a SEM image of the surface of the Si / C composite produced in Example 1. [Figure 1c]1 is a SEM image of the surface of the Si / C composite produced in Example 2. [Figure 1d] 1 is a SEM image of the surface of the Si / C composite produced in Example 3. [Figure 1e] 1 shows SEM images of graphite particles before (left SEM image) and after (right SEM image) pretreatment according to Comparative Example 2. [Figure 2a] 1 is an XRD (X-ray diffraction) graph of the Si / C composite produced in Comparative Example 1. [Figure 2b] 1 is an XRD (X-ray diffraction) graph of the Si / C composite produced in Example 1. [Figure 2c] 1 is an XRD (X-ray diffraction) graph of the Si / C composite produced in Example 2. [Figure 2d] 1 is an XRD (X-ray diffraction) graph of the Si / C composite produced in Example 3. [Diagram 3] Figure 3 is a photograph (Microwave Chemical and Materials Processing Doi.org / 10.1007 / 978-981-10-6466-1_4) showing hot spots formed on the surface of a carbon-based particle through microwave irradiation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] The advantages and features of the present invention, as well as the methods for achieving them, will become clear from the following detailed description of the embodiments in conjunction with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms, and the embodiments are provided to fully disclose the present invention and fully inform those skilled in the art of the scope of the invention, and the present invention is only defined by the scope of the claims.
[0037] Unless otherwise defined, all terms (including technical and scientific terms) used herein may be used in the sense commonly understood by those having ordinary skill in the art to which the present invention belongs. When any part in the entire specification "comprises" a certain component, this does not mean excluding other components, but may further include other components, unless otherwise specified to the contrary. In addition, the singular form includes the plural form unless otherwise specified in the phrase.
[0038] One embodiment of the present invention provides an anode active material including a silicon / carbon (Si / C) composite in which a silicon-based coating layer is formed on carbon-based particles. The present invention improves the mechanical damage of the electrode caused by the volume expansion and contraction of silicon and the resulting rapid shortening of the lifespan by combining the silicon with carbon-based particles that can buffer the volume expansion of silicon.
[0039] The Si / C composite has a peak area ratio A2 / A1 of 0.2 to 3.0 as measured by X-ray diffraction analysis, and may be, for example, 0.2 to 2.5, 0.2 to 2, 0.2 to 1.5, 0.2 to 1, 0.2 to 0.8, 0.2 to 0.7, 0.2 to 0.6, 0.2 to 0.6, 0.3 to 0.6, or 0.3 to 0.5.
[0040] The A1 is a peak area at all angles corresponding to a Si peak in X-ray diffraction analysis, and the A2 is a peak area at all angles corresponding to a SiC peak in X-ray diffraction analysis. In addition, all angles (2Theta) corresponding to the Si peak in the X-ray diffraction analysis may be 28.4±0.5°, 47.3±0.5°, 56.1±0.5°, 69.1±0.5°, 76.4±0.5° and 88.0±0.5°, and the respective crystal planes may be (111), (202), (311), (400), (313) and (422), and all angles (2Theta) corresponding to the SiC peak may be 35.6±0.5°, 41.4±0.5°, 59.9±0.5°, 71.7±0.5°, 75.5±0.5° and 89.9±0.5°, and the respective crystal planes may be (111), (020), (202), (311), (222) and (040). For reference, all angles (2Theta) corresponding to the graphite peaks may be 26.5±0.5°, 42.3±0.5°, 44.5±0.5°, 50.6±0.5°, 54.6±0.5°, 59.8±0.5°, 71.4±0.5° and 77.4±0.5°, and the respective crystallographic planes may be (002), (100), (101), (012), (004), (013), (014) and (110).
[0041] When the peak area ratio is below the upper limit, the generation of silicon carbide (SiC), which is an inactive material, may be suppressed, and the proportion of silicon nanoparticles impregnated on the surface of the carbon-based particles may increase.When the peak area ratio is above the lower limit, the carbon-based particles and the solid silicon before melting are dispersed and mixed uniformly, so that the proportion of solid silicon melted on the surface of the carbon-based particles irradiated with microwaves is high and the proportion of unreacted silicon is low, which may mean that the production efficiency of the Si / C composite is generally improved.
[0042] The surface of carbon-based particles is rapidly heated to around 1,400°C by microwaves, allowing silicon carbide (SiC), which is synthesized at high temperatures of over 900°C and is inactive to lithium ions, to be impregnated thereon.
[0043] In the present invention, the microwave absorption ability of carbon-based particles can be improved by forming a surface irregularity structure (defect) by using pretreated carbon-based particles. The improvement of microwave absorption and heat generation performance can be confirmed by the reduction in hot spot formation time on the surface of the carbon-based particles. In the present invention, the hot spot formation time is reduced and the carbon-based particles can be uniformly heated and rapidly heated / cooled overall, thereby reducing the residence time in the high temperature range where the SiC synthesis reaction occurs. In addition, the uneven surface structure (defect) of the pretreated (heat-treated) carbon-based particles can control the morphology of the molten silicon, preventing the silicon particles from becoming coarse and the connection between the particles (thinning). As a result, the physical contact area between the silicon and the carbon-based particles where the SiC synthesis reaction occurs can be reduced, thereby further reducing the amount of SiC synthesis.
[0044] In the present invention, a hot spot of a carbon-based particle means that when microwaves are irradiated onto the carbon-based particle, a uniform reaction does not occur at all positions within the same time, but a reaction occurs first at a specific portion, and such a phenomenon can be defined as a "hot spot. " In the case of a hot spot occurring on the surface of a carbon-based particle, the "hot spot time" can be measured by visual observation based on the time when the reaction first occurs.
[0045] In the Si / C composite, the Si peak area (A1) relative to 100% of the total peak area may be 2 to 7%, for example, 2.5 to 7%, 2.5 to 6.5%, 2.5 to 6%, 2.5 to 5.5%, 2.5 to 5% or 2.5 to 4% in X-ray diffraction analysis. Also, the SiC peak area (A2) relative to 100% of the total peak area may be 0.5 to 5.5%, 0.5 to 5%, 1 to 5%, 2 to 5%, 3 to 5%, 3.5 to 5%, 3.5 to 4.5% or 4 to 4.5%. This can further improve the above-mentioned effects.
[0046] The total peak area of 100% may mean the sum of the peak areas (A1) at all angles corresponding to the Si peak, the peak area (A2) at all angles corresponding to the SiC peak, and the peak area (A3) at all angles corresponding to the graphite peak.
[0047] The Si / C composite has a BET specific surface area (B2) of 8m 2 / g or more, for example, 8 to 23 m 2 / g, 8-20m 2 / g, 8-17m 2 / g, 8-15m 2 / g, 8-14m 2 / g, 8-13m 2 / g, 9-13m 2 / g or 9~12m 2 / g.
[0048] When a silicon-carbon composite is produced using microwaves, silicon is impregnated only on the surface of the carbon-based particles heated by microwave irradiation, and it is analyzed that silicon melted by the microwave calcination reaction does not block the uneven structure and pore structure of the surface of the pretreated carbon-based particles. It was confirmed that the BET specific surface area of the Si / C composite finally produced after the microwave calcination reaction can be adjusted to a relatively high level compared to before the reaction. In addition, when the BET specific surface area falls within the above range, it means that silicon particles are uniformly dispersed in nano-size and impregnated on the surface of the carbon-based particles, and when it is below the lower limit, it means that silicon particles in the form of a thin film are impregnated, and when it exceeds the upper limit, the particle structure collapses and the basal plane of graphite is exposed, which may cause electrolyte side reactions due to an excessive increase in the specific surface area.
[0049] The Si / C composite may have a BET specific surface area ratio B2 / B1 of 1 or more, for example, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, or 1.5 or more and 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, or 2.0 or less. The B1 is the BET specific surface area of the carbon-based particles in the Si / C composite before the silicon-based coating layer is formed, and the B2 is the BET specific surface area of the Si / C composite (after the silicon-based coating layer is formed).
[0050] When the BET specific surface area ratio B2 / B1 is equal to or greater than the lower limit, the proportion of molten silicon impregnated in the form of nanoparticles on the surface of the carbon-based particles irradiated with microwaves increases, which may mean that the coarsening of silicon particles and the connection between particles (thinning) are controlled (prevented). On the other hand, when the particle size of silicon impregnated on the surface of the carbon-based particles increases or the silicon particles are connected to form a thin film (network shape), the BET specific surface area can be reduced by the silicon coating layer. In addition, when the BET specific surface area ratio B2 / B1 is equal to or less than the upper limit, the proportion of solid silicon melted on the surface of the carbon-based particles irradiated with microwaves increases and the proportion of unreacted silicon decreases, which may mean that the overall manufacturing efficiency of the Si / C composite is improved.
[0051] The Si / C composite may have a specific surface area contribution ratio (B2_C) of the carbon-based particles of 50 to 89.5% relative to a total BET specific surface area (B2) of 100%, and the specific surface area contribution ratio (B2_Si) of the silicon-based coating layer of 10.5 to 50%. Here, the specific surface area contribution ratio (B2_C) of the carbon-based particles is calculated by measuring the BET specific surface area of graphite (pretreated graphite) that is treated in the same manner with microwaves except that no Si powder is used, and calculating the percentage of the BET specific surface area of the Si / C composite. The specific surface area contribution ratio (B2_Si) of the silicon coating layer is a value obtained by subtracting the ratio of the specific surface area of the carbon-based particles from the BET specific surface area of the total Si / C composite of 100%.
[0052] For example, the Si / C composite may have a contribution rate (B2_C) of the carbon-based particles of 50-85%, 55-80%, 60-80% or 65-75% relative to a total BET specific surface area (B2) of 100%, and the contribution rate (B2_Si) of the silicon coating layer may be 15-50%, 20-45%, 20-40% or 25-35%.
[0053] As the contribution rate (B2_Si) of the silicon coating layer increases and the contribution rate (B2_C) of the carbon-based particles decreases, the rate at which the molten silicon is impregnated in the form of nanoparticles on the surface of the microwave-irradiated carbon-based particles may increase. Conversely, as the contribution rate (B2_Si) of the silicon coating layer decreases and the contribution rate (B2_C) of the carbon-based particles increases, the increase in the total BET specific surface area may mean that unreacted silicon increases due to a morphological change on the surface of the microwave-irradiated carbon-based particles.
[0054] The carbon-based particles may be at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers, and hard carbon, and are preferably natural graphite or artificial graphite. The carbon-based particles may be single particles or secondary particles formed by agglomeration of multiple particles.
[0055] The carbon-based particles may have an average particle size (D50) of 5 to 30 μm, 5 to 20 μm, or 10 to 20 μm, an average particle size (D10) of 3 to 20 μm, 3 to 15 μm, or 5 to 15 μm, and / or an average particle size (D90) of 15 to 35 μm, 15 to 30 μm, or 20 to 25 μm.
[0056] In addition, the carbon-based particles may be spherical, plate-like or acicular particles, and by adjusting the material structure (porous, hollow, core-shell, multi-layer and hierarchical) to form plate-like or acicular particles, the microwave propagation path can be expanded, thereby further improving the absorption capacity of the microwave absorber.
[0057] The conditions for controlling the heating of carbon-based particles by microwaves include the type, content and particle shape of the carbon material, and when the type, average particle size and shape of the carbon-based particles fall within the range of the present invention, the microwave absorption capacity can be improved.
[0058] The carbon-based particles are measured using a color difference meter. * The value may be 35 or less, for example, the L * The value may be 34 or less, 33 or less, or 32 or less. The lower limit is not particularly limited, and may be, for example, 10 or more, 20 or more, 25 or more, or 30 or more.
[0059] The term "color difference meter L" used in this invention * Value" is L * a * b * In the chromaticity coordinates, the L value may indicate the brightness. The L value may be expressed from 0 to 100, with values closer to 0 indicating black and values closer to 100 indicating white. In the present invention, the heat-treated carbon-based particles have an increased light absorption due to the surface irregularity structure (defects), and the L value of the color difference meter is * The L value of the color difference meter of the carbon-based particles can be reduced. * When the value falls within the design range, the heat generation performance of the carbon-based particles is improved through the formation of a surface irregularity structure (defects) on the heat-treated carbon-based particles, and the morphology of the molten silicon can be controlled by the surface irregularity structure (defects) on the heat-treated carbon-based particles, thereby preventing the coarsening of silicon particles and the connection between silicon particles (thinning).
[0060] The equipment for measuring the color difference meter value is not limited, and may be, for example, a spectrophotometer, a color difference meter, a color reader, a colorimeter, etc. For example, the color difference meter value may be measured using a Chroma Meter CR-410 KONIKA MINOLTA measuring instrument.
[0061] The silicon-based coating layer may include silicon (Si) particles having a size of 10 to 100 nm. Specifically, the silicon nanoparticles included in the silicon-based coating layer may have a particle size (D50) of 10 to 100 nm or 20 to 100 nm. In the present invention, the morphology of molten silicon on the surface of the particles can be controlled by using pretreated carbon-based particles having a roughness structure (defect) formed on the surface. As a result, the coarsening of silicon particles and the connection between particles (thinning) can be prevented.
[0062] The silicon (Si) particle size may refer to the size (D50) measured by cumulative volume. Unless otherwise defined in this specification, D50 refers to the average size, which means the diameter of pores with a cumulative volume of 50% by volume in particle size distribution. The average size (D50) may be measured by a method widely known to those skilled in the art, for example, by a transmission electron microscope photograph or a scanning electron microscope photograph. As another method, the average size (D50) value may be obtained by measuring using a measuring device using dynamic light-scattering, performing data analysis, counting the number of pores for each pore size range, and then calculating from this.
[0063] The silicon-based coating layer may be included in an amount of 1 to 50% by weight, for example, 1 to 40% by weight, 1 to 30% by weight, 5 to 30% by weight, or 5 to 20% by weight, based on the total weight of the Si / C composite. The silicon-based coating layer may be formed to a thickness of 10 to 200 nm, for example, 10 to 180 nm, 10 to 160 nm, 10 to 150 nm, or 10 to 130 nm.
[0064] The Si / C composite may further include a carbon coating layer located on the silicon coating layer. Direct exposure of silicon in the silicon-based coating layer to the electrolyte may be minimized to reduce electrolyte side reactions, and the volume expansion of silicon particles may be further buffered to improve the life characteristics of the battery. The carbon coating layer may be formed to a thickness of 0.01 μm or more, for example, 0.03 μm or more or 0.05 μm or more and 10 μm or less, 5 μm or less, or 1 μm or less. This may further improve the above-mentioned effects.
[0065] Hereinafter, a method for manufacturing a negative electrode active material for a secondary battery will be provided. The method may be a method for manufacturing the negative electrode active material according to an embodiment of the present invention.
[0066] The method for producing the negative electrode active material for a secondary battery includes a pretreatment step of heat-treating carbon-based particles, and a microwave firing step of mixing the heat-treated carbon-based particles and silicon-based particles and irradiating the mixture with microwaves.
[0067] The pretreatment step is a step of heat-treating the carbon-based particles at 400-900°C for 1-10 hours. The purpose is to improve the heat generation performance of the carbon-based particles in the sintering step of irradiating microwaves by forming a rough structure (defect) on the surface of the carbon-based particles. The heat generation performance of the carbon-based particles can be improved by forming a rough structure (defect) on the surface of the heat-treated carbon-based particles. The pretreatment step may be, for example, a heat treatment in an air atmosphere at a temperature rise rate of 1-10°C / min or 2-7°C / min and at a reactor temperature of 400-800°C, 400-700°C, or 400-600°C for 1-6 hours, 2-6 hours, or 3-6 hours.
[0068] The pretreatment step is a step of heat-treating carbon-based particles, and is characterized in that the heat treatment is performed so that the weight reduction rate of the carbon-based particles before and after the heat treatment (weight of carbon-based particles after heat treatment / weight of carbon-based particles before heat treatment x 100 (%)) is more than 1 wt% and less than 40 wt%, more than 5 wt% and less than 30 wt%, more than 10 wt% and less than 25 wt%, more than 14 wt% and less than 25 wt%, or more than 15 wt% and less than 20 wt%.
[0069] The firing step is a step of mixing the heat-treated carbon-based particles and silicon-based particles to obtain a mixture in which the silicon-based particles are dispersed on the surfaces of the carbon-based particles, and rapidly heating the surfaces of the heat-treated carbon-based particles of the mixture with microwaves, so that the silicon-based particles melt due to the carbon-based particles heated by the microwaves, thereby forming a silicon-based coating layer on the surfaces of the carbon-based material.
[0070] The mixing can be performed using a particle mixer at 500 to 2000 rpm or 700 to 1500 rpm for 1 to 10 minutes. The particle mixer can be, but is not limited to, a rotary mixer, a revolution mixer, a blade mixer, or a particle fusion machine.
[0071] The carbon-based particles and silicon-based particles can be mixed in a weight ratio of 99:1 to 60:40, 99:1 to 70:30, 95:5 to 70:30, or 95:5 to 80:20.
[0072] The carbon-based particles may be natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers, hard carbon, or a combination thereof, and the silicon-based particles may be silicon particle powder having a size of 10 nm to 10 μm, 100 nm to 10 μm, or 100 nm to 5 μm.
[0073] The microwave heating may be performed by irradiating microwaves (wavelength, 1 m to 1 mm; frequency, 300 MHz to 300 GHz) at an output of 1 to 3 kW for 10 seconds to 10 minutes, 30 seconds to 2 minutes, or 30 seconds to 60 seconds. The microwave heating may be performed by heating the surface of the carbon-based particles to 1400°C or higher within 1 minute, for example, within 30 seconds or within 10 seconds. When irradiating the heat-treated carbon-based particles with microwaves, the microwave absorption performance and heat generation performance are improved through the formation of an uneven structure (defect) on the surface of the heat-treated carbon-based particles, thereby shortening the hot spot formation time on the particle surface. In the present invention, the hot spot formation time can be shortened to 5 to 30 seconds, 5 to 25 seconds, 5 to 20 seconds, 10 to 20 seconds, or 10 to 15 seconds. Referring to FIG. 3, the term "hot spot" refers to a phenomenon where a reaction does not occur uniformly at all locations during microwave (MW) irradiation, but occurs first in a certain area, and in the present invention, it refers to the phenomenon where heat generation is observed first. The hot spot time was measured by measuring the time from the moment when the heat generation location was visually observed as shown in FIG. 3. In the present invention, a defect is formed on the surface of the pretreated graphite particles, thereby improving the microwave absorption ability. This improves the surface heat generation characteristics of the carbon particles during microwave irradiation, thereby shortening the time when the heat generation phenomenon is observed.
[0074] After the microwave firing step, a cooling step may be further included to prevent the crystallinity of the silicon-based material impregnated on the surface from increasing due to the thermal energy remaining in the carbon-based particles. The cooling step may be performed at room temperature or at a temperature of -10 to 10°C and under normal pressure, and may be performed in a cooled reactor into which nitrogen gas is injected.
[0075] Another embodiment of the present invention provides a negative electrode for a secondary battery and a secondary battery comprising the negative electrode active material.
[0076] The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector, and the negative electrode active material according to an embodiment of the present invention is present in the negative electrode active material layer.
[0077] The negative electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. The negative electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the negative electrode active material. Such a negative electrode current collector can be provided in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0078] The negative electrode active material layer may be a layer containing the above-mentioned negative electrode active material as well as a conductive material and a binder.
[0079] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has conductivity without causing a chemical change in the negative electrode active material. Non-limiting examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives. The conductive material may be generally included in an amount of 1 wt % to 30 wt % based on the total weight of the negative electrode active material layer.
[0080] The binder is a material that improves adhesion between negative active material particles and adhesion between the negative active material and the current collector. Non-limiting examples of the binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof. The binder may be typically included in an amount of 1 wt% to 30 wt% based on the total weight of the negative active material layer.
[0081] The negative electrode according to an embodiment of the present invention may be manufactured by a method for manufacturing a negative electrode for a secondary battery, except that the negative electrode active material is used. For example, a negative electrode may be manufactured by selectively coating a negative electrode active material layer forming slurry, including a negative electrode active material, a binder, and a conductive material, on a negative electrode current collector, followed by drying and rolling. According to another example, a negative electrode may be manufactured by casting the negative electrode active material layer forming slurry on a separate support, peeling the negative electrode active material layer from the support, and laminating the resulting film on a negative electrode current collector.
[0082] According to yet another aspect of the present invention, there is provided an electrochemical device including the above-mentioned negative electrode, wherein the electrochemical device may be specifically a battery, a capacitor, or the like, more specifically a lithium secondary battery.
[0083] The secondary battery includes a negative electrode, a positive electrode facing the negative electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte (electrolytic solution). The lithium secondary battery may also include a battery container (case) that houses the electrode assembly including the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0084] Depending on the shape of the battery container (case), lithium secondary batteries can be classified into can-type lithium secondary batteries in which the electrode assembly is housed in a metal can, and pouch-type lithium secondary batteries in which the electrode assembly is housed in a pouch made of a sheet such as an aluminum laminate.
[0085] The present invention will be described in detail below with reference to examples. However, these are for the purpose of explaining the present invention in more detail, and the scope of the present invention is not limited to the following examples. Working Example Production Example 1. Production of Si / C composite negative electrode active material <Examples 1 to 3 and Comparative Example 1> Stage 1: Graphite pretreatment 20 g of natural graphite (D50: 15 μm) was weighed into a crucible and then placed in a tube furnace. The crucible was heated at 560°C for 1 to 5 hours in an air atmosphere at a temperature rise rate of 5°C / min to obtain pretreated graphite. The weight loss rate of the graphite after pretreatment compared to the graphite before pretreatment is shown in Table 1 below. (Heat treatment time = Example 1: 1 hour, Example 2: 4 hours, Example 3: 5 hours, Comparative Example 1: no heat treatment, Comparative Example 2: 7 hours)
[0086] Step 2: Si / C composite through microwave irradiation The pretreated natural graphite and plate-shaped Si particles (D50:400nm) powder were charged into a super mixer in a weight ratio of 9:1 and mixed at 1000 rpm for 10 minutes. Next, 2450MHz microwaves were irradiated at an output of 1kW for 60 seconds. The hot spot formation time is shown in Table 1 below.
[0087] Then, cooling was performed at -5°C / min to prepare a Si / C composite negative electrode active material in which a silicon coating layer was formed on the pretreated natural graphite. Here, the hot spot formation time was measured as the time when the first reaction (hot spot) occurred on the surface of the carbon-based particle, and reflected the results of visual observation as shown in FIG. [Table 1]
[0088] Manufacturing Example 2. Manufacturing of lithium secondary batteries The negative electrode active material (96 wt%), carbon black (1 wt%), SBR binder (1.5 wt%), and carboxymethyl cellulose (1.5 wt%) were dispersed in distilled water (30 g) to prepare a negative electrode slurry. The negative electrode slurry was uniformly applied to a Cu thin film and dried in vacuum at 135°C to prepare a negative electrode for a lithium secondary battery.
[0089] LiNi 0.9 Co 0.1 Mn 0.1 A positive electrode slurry was prepared by mixing 94 wt% O2 (NCM911, EcoPro BM), 3 wt% carbon black, and 3 wt% PVdF binder with N-methyl-2-pyrrolidone. The positive electrode slurry was uniformly applied to an Al thin film, vacuum dried at 135°C, and then rolled to prepare a positive electrode for a lithium secondary battery.
[0090] The prepared positive and negative electrodes and a porous polyethylene membrane (Celgard 2300, thickness: 25μm) separator were placed in a battery container, and a lithium secondary battery was manufactured using an electrolyte solution containing LiPF6 at a concentration of 1.15M in a solvent containing EC:EMC mixed at a volume ratio of 3:7.
[0091] Experimental Example Experimental Example 1: Confirmation of the shape of the silicon coating layer on the carbon particle surface by SEM image analysis 1a to 1d are SEM images of the surfaces of the Si / C composite particles produced in Comparative Example 1, Example 1, Example 2, and Example 3, respectively. 1a to 1d, it was confirmed that the Si / C composites produced in Examples 1 to 3 had Si nanoparticles of 1 to 100 nm in size uniformly impregnated on the graphite surface. In particular, it was confirmed that the deposition rate of spherical Si nanoparticles on the graphite surface increased as the graphite weight loss rate and the graphite heat treatment time increased within a preferred range. On the other hand, in the case of Comparative Example 1, it was confirmed that the silicon deposition form and its size were not uniform due to the coarsening of the Si particle size and the connected structure (network structure) between the particles.
[0092] Experimental Example 2: Evaluation of the characteristics of carbon-based particles and the surface characteristics of Si / C composites depending on the heat treatment conditions of carbon-based particles The BET specific surface areas of the Si / C composites produced in Comparative Examples 1 and 2 and Examples 1 to 3 were measured by the BET method, and the results are summarized in Table 2 below. In Table 2 below, "Pretreated graphite (B1)" is the BET specific surface area value of pretreated graphite (graphite before the silicon-based coating layer is formed on the Si / C composite) produced in step 1. "Si / C composite (B2)" is the BET specific surface area value of the Si / C composite produced in step 2. "Microwave-treated graphite (R)" is the BET specific surface area value of microwave-treated (pretreated) graphite produced in the same manner as step 2 (microwave irradiation) except that Si powder was not used.
[0093] The ratio of specific surface areas (B2 / B1) is the calculated value of the BET specific surface area (B2) of the Si / C composite after the formation of the silicon-based coating layer relative to the BET specific surface area (B1) of the carbon-based particle before the formation of the silicon-based coating layer.
[0094] The specific surface area ratio (B2 / R) is the BET specific surface area (B2) of the Si / C composite after forming a silicon-based coating layer relative to the BET specific surface area (R) of microwave-treated (pretreated) graphite prepared in the same manner as in step 2 (microwave irradiation) except that no Si powder was used.
[0095] The specific surface area contribution ratio (B2_C) was calculated as a percentage of the BET specific surface area of the Si / C composite by measuring the BET specific surface area of graphite (pretreated graphite) that was treated with microwaves in the same manner except that no Si powder was used; specifically, it is the percentage of the BET specific surface area (R) of the microwave-treated graphite relative to the BET specific surface area (B2) of the Si / C composite.
[0096] [Table 2] Referring to Table 2, the Si / C composites produced in all the examples had a BET specific surface area (B2) of 9.5 m compared to Comparative Example 1. 2 / g or more, and as the weight loss rate of graphite and the heat treatment time of graphite increase within a preferred range, the BET specific surface area tends to increase.
[0097] In the case of the ratio of specific surface areas (B2 / B1), in Comparative Example 1, it was 2.7 m 2 / g, and showed a tendency to decrease as the weight loss rate of graphite increased (Example 1 → Comparative Example 2). In the case of the specific surface area contribution rate (B2_C), it was relatively high in Comparative Examples 1 and 2, and in the Examples, it tended to decrease as the weight reduction rate of graphite increased (Example 1 → Example 3). In particular, it was confirmed that in Examples 2 to 3, the specific surface area contribution rate of carbon (B2_C) decreased significantly compared to Comparative Examples 1 and 2 and Example 1.
[0098] When non-pretreated graphite is used (Comparative Example 1), the proportion of the increase in specific surface area due to microwave calcination that is due to changes in the surface morphology of the graphite is higher than in the Examples, so it is analyzed that there is a relative increase in unreacted silicon in Comparative Example 1. In addition, the total BET specific surface area (B2) of the Si / C composite is significantly smaller in Comparative Example 1 than in the Examples, so it is analyzed that there is a high proportion of silicon particles coarsening and impregnation in the form of interparticle connections.
[0099] On the other hand, when pretreated graphite is used (Examples 1-3), it is possible to improve heat generation performance through the surface defects of the carbon-based particles and control the morphology of the silicon melt, resulting in a higher rate of silicon being impregnated in the form of nanoparticles. These analysis results are consistent with the SEM images in Figures 1a-1d.
[0100] In addition, Fig. 1e is an SEM image of graphite particles before (left SEM image) and after (right SEM image) pretreatment according to Comparative Example 2. Referring to Fig. 1e and Table 2, it is analyzed that when the weight reduction rate of the pretreated graphite reaches 40%, the particle structure collapses, the heat generation performance is excessively improved, the SiC crystal phase increases, the proportion of Si deposited in the form of a thin film increases, and the BET increase rate decreases.
[0101] Experimental Example 3: XRD analysis of Si / C composite and evaluation of electrochemical properties of lithium secondary battery XRD analysis was performed using a Bruker D8 ADVANCE A25, with a voltage of 45 kV and a current of 30 mA applied. Analysis of each phase was compared with COD No. 4104917 (Si), 1011031 (SiC), and 9011577 (graphite). The results confirmed all peak positions corresponding to each crystal phase. Peak information for each crystal phase is shown in Table 3 below.
[0102] The peaks thus obtained (FIGS. 2a to 2d) were deconvoluted to determine the peak area A1 (%) corresponding to Si and the peak area A2 (%) corresponding to SiC. The measurement results are shown in Table 4 below.
[0103] The electrochemical characteristics were analyzed by measuring the initial charge capacity, initial discharge capacity, and initial efficiency (ICE) through charge-discharge experiments at 25° C., voltage range of 0.005 V to 1.5 V, and C rate of 0.1 C to 0.5 C using an electrochemical analyzer (Shincorp, Toscat-3100). The measurement results are shown in Table 4 below.
[0104] [Table 3] [Table 4]
[0105] Referring to Table 4, in the case of the lithium secondary batteries prepared in Examples 1 to 3, it was confirmed that the generation of the inactive material SiC was suppressed when heat-treated graphite was used, and the charge / discharge capacity and initial efficiency were improved.
[0106] In addition, in the case of Comparative Example 2, when excessively pretreated graphite was used, the particle structure collapsed and the basal plane of the graphite was exposed, and therefore, it was analyzed that the initial Coulombic efficiency was reduced due to exposure to excessive electrolyte.
[0107] As described above, the present invention has been illustrated and described with reference to specific embodiments. However, it will be apparent to those skilled in the art that the present invention can be modified and changed in various ways without departing from the technical spirit of the present invention as defined by the following claims.
Claims
1. The present invention includes a silicon / carbon (Si / C) composite having a silicon-based coating layer formed on a carbon-based particle, The Si / C composite is a negative electrode active material characterized in that the peak area ratio A2 / A1 as measured by X-ray diffraction analysis is 0.2 to 3.
0. (A1 is the area of the Si peak in the X-ray diffraction analysis, and A2 is the area of the SiC peak in the X-ray diffraction analysis)
2. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the Si / C composite has a peak area ratio A2 / A1 of 0.3 to 0.5 as determined by X-ray diffraction analysis. (A1 is the area of the Si peak in the X-ray diffraction analysis, and A2 is the area of the SiC peak in the X-ray diffraction analysis)
3. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the Si / C composite has a Si peak area (A1) of 2 to 7% and a SiC peak area (A2) of 0.5 to 5.5% relative to a total peak area of 100% in an X-ray diffraction analysis.
4. The Si / C composite has a BET specific surface area (B2) of 8 m 2 The negative electrode active material for a secondary battery according to claim 1 , wherein the molecular weight of the negative electrode active material is 1 / g or more.
5. The Si / C composite has a BET specific surface area (B2) of 8 to 23 m 2 The negative electrode active material for a secondary battery according to claim 1 , wherein the molecular weight of the negative electrode active material is 1 / g.
6. The negative electrode active material for a secondary battery according to claim 1 , wherein the Si / C composite has a BET specific surface area ratio B2 / B1 of 1 or more. (B1 is the BET specific surface area of the carbon-based particles before forming the silicon-based coating layer on the Si / C composite, and B2 is the BET specific surface area of the Si / C composite).
7. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the Si / C composite has a BET specific surface area ratio B2 / B1 of 1.2 to 2.
5. (B1 is the BET specific surface area of the carbon-based particles before forming the silicon-based coating layer in the Si / C composite, and B2 is the BET specific surface area of the Si / C composite)
8. The Si / C composite has a total BET specific surface area (B2) of 100%, 2. The negative electrode active material for a secondary battery according to claim 1, wherein the specific surface area contribution rate (B2_C) of the carbon-based particles is 50 to 89.5%, and the specific surface area contribution rate (B2_Si) of the silicon-based coating layer is 10.5 to 50%.
9. The Si / C composite has a total BET specific surface area (B2) of 100%, 2. The negative electrode active material for a secondary battery according to claim 1, wherein the BET specific surface area contribution rate (B2_C) of the carbon-based particles is 60 to 80%, and the BET specific surface area contribution rate (B2_Si) of the silicon-based coating layer is 20 to 40%.
10. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the silicon-based coating layer contains silicon nanoparticles having a size of 1 to 100 nm.
11. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the silicon-based coating layer is included in an amount of 5 to 50 wt % based on the total weight of the Si / C composite.
12. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the silicon-based coating layer is formed to a thickness of 10 to 200 nm.
13. 2. The negative electrode active material for a secondary battery according to claim 1, wherein the carbon-based particles are at least one selected from the group consisting of natural graphite, artificial graphite, expanded graphite, graphene oxide, carbon nanotubes, carbon fibers, and hard carbon.
14. The carbon-based particles are L * The negative electrode active material for a secondary battery according to claim 1 , wherein the value is 35 or less.
15. A pretreatment step of heat treating the carbon-based particles; and mixing the heat-treated carbon-based particles and silicon-based particles, followed by irradiating the mixture with microwaves to perform a microwave firing step.
16. 16. The method of claim 15, wherein the pretreatment step comprises heat-treating the carbon-based particles at 400 to 900° C. for 1 to 10 hours.
17. 16. The method of claim 15, wherein the microwave calcination step comprises rapidly heating surfaces of the heat-treated carbon-based particles with microwaves, and melting the silicon-based particles by the microwave-heated carbon-based particles to form a silicon-based coating layer on the surface of the carbon-based material.
18. The method for producing a negative electrode active material for a secondary battery according to claim 15, wherein the microwave heating is performed by irradiating microwaves with an output of 1 to 3 kW for 10 seconds to 10 minutes.
19. A negative electrode for a secondary battery comprising the negative electrode active material according to claim 1 .
20. A secondary battery comprising the negative electrode of claim 19.
Citation Information
Patent Citations
Si / C COMPOSITE, ANODE ACTIVE MATERIAL CONTAINING THE SAME, AND LITHIUM BATTERY
JP2009032693A
silicon-carbon composite particle material
JP2018520494A
Novel material having highly durable lithium insertion and method for manufacturing the same
JP2018534720A
Method of manufacturing composite anode material and composite anode material for lithium secondary battery
JP2020174033A
Negative electrode active material, its manufacturing method, and lithium secondary battery having a negative electrode containing the same
JP2022508339A